2013
DOI: 10.1126/science.1238286
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Comparison of Medieval and Modern Mycobacterium leprae

Abstract: Leprosy: Ancient and Modern In medieval Europe, leprosy was greatly feared: Sufferers had to wear bells and were shunned and kept isolated from society. Although leprosy largely disappeared from Europe in the 16th century, elsewhere in the world almost a quarter of a million cases are still reported annually, despite the availability of effective drugs. Schuenemann et al. (p. 179 , published online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
420
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(455 citation statements)
references
References 68 publications
27
420
1
7
Order By: Relevance
“…Those analyses dated human infections in Israel to 9000 years ago [59] and tuberculosis of wild bison in North America to 17 000 years ago [60]. It has been suggested that aDNA from Mycobacterium is less exposed to DNA damage than that of other bacterial taxa, because mycobacterial cell walls contain mycolic acid [61]. This explanation could explain an unusually high success rate for the PCR amplification of aDNA from M. tuberculosis.…”
Section: How Long Have Humans Been Afflicted By Tuberculosis?mentioning
confidence: 99%
“…Those analyses dated human infections in Israel to 9000 years ago [59] and tuberculosis of wild bison in North America to 17 000 years ago [60]. It has been suggested that aDNA from Mycobacterium is less exposed to DNA damage than that of other bacterial taxa, because mycobacterial cell walls contain mycolic acid [61]. This explanation could explain an unusually high success rate for the PCR amplification of aDNA from M. tuberculosis.…”
Section: How Long Have Humans Been Afflicted By Tuberculosis?mentioning
confidence: 99%
“…53 Similar work is commencing with leprosy. 54,55 Scientific evidence should nevertheless be historicised just as rigorously as other forms of historical evidence. 38,56,57 By confirming both the historical presence of pathogens and their evolution, scientific evidence has reinvigorated the humanist narrative of disease history.…”
Section: Discussionmentioning
confidence: 99%
“…Next generation sequencing as applied to ancient DNA has improved our understanding of the evolutionary history of pathogenic bacteria and the phylogeographic distribution of their associated diseases [1][2][3][4][5][6]. Thus far, most genomic analyses have relied on molecular capture techniques designed to target DNA from individual organisms suspected to have left molecular traces in preserved tissues.…”
Section: Introductionmentioning
confidence: 99%